Crystal structure of bis[octakis(dimethyl sulfoxide-κO)ytterbium(III)] pentabromidoplumbate(II) tribromide dimethyl sulfoxide monosolvate: a ytterbium-doped lead halide perovskite precursor - Takumi Kinoshita; Kanna Fukumoto; Hiroshi Segawa (Acta Crystallographica Section E: Crystallographic Communications, 2023)
A mixture of PbBr2 and YbBr3·nH2O in a dimethyl sulfoxide (DMSO) solution yielded single crystals of a lead halide perovskite precursor with ytterbium, bis[octakis(dimethyl sulfoxide)ytterbium(III)]pentabromidoplumbate(II) tribromide with dimethyl sulfoxide as co-crystallite, [Yb(C2H6OS)8][PbBr5]0.5Br1.5·0.5C2H6OS. The complex ions PbBr53− and Yb(DMSO)83+ are present in the crystal together with three Br− ions and DMSO molecules. X-ray crystallography revealed that the Br− ions in YbBr3 are replaced by the solvent and bound to a PbII atom or remain free. The presence of PbBr53− units, which are molecular ions with a square-pyramidal structure, is also observed. These single crystals react with a caesium chloride solution, exhibiting near-infrared (NIR) luminescence by visible photoexcitation, suggesting the formation of Yb3+-doped lead halide perovskites (CsPbBr3-xClx·Yb3+).